2007
DOI: 10.1007/s11695-007-9042-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Maximum Roux-en-Y Gastric Bypass-Induced Weight Reduction — Preoperative Plasma Leptin or Body Weight?

Abstract: Preoperative plasma leptin concentration cannot be used as a predictor of weight reduction following RYGBP. Preoperative body weight is a reliable predictor of post-RYGBP weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
(26 reference statements)
7
20
0
1
Order By: Relevance
“…A recent study showed that preoperative plasma leptin concentration cannot be used as a predictor of weight reduction after RYGBP [10]. Our result was consistent with their study that the baseline leptin level was not predictive of %EBL 1 year after LMGBP surgery.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A recent study showed that preoperative plasma leptin concentration cannot be used as a predictor of weight reduction after RYGBP [10]. Our result was consistent with their study that the baseline leptin level was not predictive of %EBL 1 year after LMGBP surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies showed that larger BMI had increased odds of below average %EWL and lower baseline weight predicted greater weight loss [6,8,9,28]. On the other hand, some studies showed that larger baseline body weight was associated with greater maximum absolute weight reduction [10]. Our study was consistent with the former studies that larger initial BMI was associated with lesser %EBL after LMGBP [6,8,9,28].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations